1980
DOI: 10.1177/1077727x8000800302
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Child‐Feeding Attitudes, and Reactive Eating: An Intergenerational Study

Abstract: Body fat, anxiety‐related overeating, and child‐feeding attitudes among 221 college women were studied along with child‐feeding attitudes of the students' mothers. The Child‐Feeding Opinion Questionnaire (CFOQ) was developed to assess attitudes toward the use of food as (a) a reward, (b) a punishment, (c) a soothing agent, and (d) an expression of affection. A six‐item reactive overeating scale was developed to assess the magnitude and frequency of anxiety‐ related overeating among the college students. Anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
3
6
0
Order By: Relevance
“…(1980). The present study agrees with others in the literature Owen & Kram, 1974;Rogers et al,1980) that both fathers and mothers tend to use food as a reward for their r children's behavior. In addition, mothers and fathers who tend to regard favorably the use of food as a reward also tend to regard its use as a soothing agent and an expression of affection in a favorable way.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…(1980). The present study agrees with others in the literature Owen & Kram, 1974;Rogers et al,1980) that both fathers and mothers tend to use food as a reward for their r children's behavior. In addition, mothers and fathers who tend to regard favorably the use of food as a reward also tend to regard its use as a soothing agent and an expression of affection in a favorable way.…”
Section: Discussionsupporting
confidence: 93%
“…Instrumentation For the purpose of this study, attitude is defined as an enduring system of positive or negative evaluations, emotional feelings, and pro or con tendencies with respect to a social object (Krech, Crutchfield, & Eallachey,1962). To determine the child-feeding attitudes of fathers, the study utilized a child-feeding opinion questionnaire based on one developed by Rogers et al (1980). The original questionnaire was a Likert-type, 55-item instrument designed to assess the child-feeding attitudes of mothers and their college-age daughters.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether similar 'food myths' might be transmitted from parent to child has yet to be explored. A study on obesity, which included measures of attitudes towards child-feeding among college women and their parents (Rogers et al 1980), showed a degree of concordance on the use of food as a punishment (i.e. withholding food (r 0-20) and for soothing ( r 0.15) but not for the other two attitudinal items.…”
Section: Cognitive Factors I N Food Choicementioning
confidence: 99%